THE INFLUENCES OF APPLIED STRESS, TEST TEMPERATURE AND CONCENTRATION ON ENVIRONMENT INDUCED CRACKING OF Ni3(Si,Ti) INTERMETALIC COMPOUND IN NEUTRAL SODIUM CHLORIDE SOLUTIONS - priyotomo, gadang (LIPI Press, 2015)
The environment-induced cracking (EIC) behavior of Ni3(Si,Ti) intermetallic compound was investigated as the function of applied stress, test temperature, and chloride-ion concentration in NaCl solution using a constant load method. From the applied stress dependence of the three parameters ( tf, lss and tss/tf ), the relationships were found to be divided into three regions: stress, EIC, and corrosion dominated regions. The ratio of tss/tf in the EICdominated region was independent constant of applied stress, test temperature, and chloride-ion concentration. Furthermore, the relationship between log tf and log lss in the EIC-dominated region became a good straight line, irrespective of applied stress, test temperature, and chloride-ion concentration. The fracture appearance in the EIC dominated region was intergranular. On the basis of the results obtained, an intergranular EIC was supposed to be influenced by hydrogen entry, dissolution, and film formation.